Blades of glory [videorecording (DVD)] - Cox, Craig; Cox, Jeff, 1976-; Philipps, Busy, 1979-; Altschuler, John; Krinsky, Dave, approximately 1963-; Ferrell, Will, 1967-; Heder, Jon, 1978-; Arnett, Will; Poehler, Amy, 1971-; Fischer, Jenna, 1974-; Fichtner, William; Nelson, Craig T. (Paramount Home Entertainment, 2007)
Bitter mens figure skating rivals Chazz Michael Michaels and Jimmy MacElroy brawl after tying for the gold medal at the world championships. Banned for life from the men's single skating competition, these archrivals find a loophole that will allow them to skate again as a figure skating pair.